M-Learning:Mobilising learning in higher education. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)
The latest teaching-learning approach in mobile learning is known as learning through mobile computational devices (Quinn, 2001), or network-based learning content (Malinen, Kari and Tiusanen, 2003). The emergence of this new pedagogical approach which promotes student centered learning experience using technologies based on mobile-learning offers opportunities, convenience, advantages and dynamic environment enabling students to succeed in their studies. This article briefly describes mobile-learning and discusses its benefits, challenges and prospects in the future education curriculum.